Reward-Related Decision-Making in Current and Past Disordered Gambling: Implications for Impulsive Choice and Risk Preference in the Maintenance of Gambling Disorder - Schluter, Magdalen G.; Hodgins, David C. (Frontiers in Behavioral Neuroscience, 2021)
Impulsive reward-related decision-making is robustly associated with Gambling Disorder (GD), although its role in the development and perpetuation of GD is still being investigated. This project sought to examine the possible roles of impulsive and risky choice, two aspects of reward-related decision-making (RRDM), in the perpetuation of GD. Additionally, the potential moderating role of comorbid substance misuse was considered. 434 participants with symptoms of current GD and symptoms of concurrent substance use disorder (SUD; n = 105), current GD with past SUD (n = 98), past GD with current SUD (n = 53), or past GD with past substance use disorder (SUD; n = 92) and 96 healthy controls were recruited through MTurk. Participants completed a randomly adjusting delay discounting (a measure of impulsive choice) and probabilistic discounting (a measure of risky choice) task and self-report questionnaires of gambling participation, GD and SUD symptomology, and trait impulsivity. Although control participants showed significantly steeper delay discounting compared to individuals with a current or history of GD, no significant group differences emerged between individuals with current GD or a history of GD. Individuals with current GD showed significantly shallower probabilistic discounting compared to individuals with a history of GD and control participants showed the steepest rates of probabilistic discounting. These effects remained after controlling for lifetime gambling symptom severity and trait impulsivity. Overall, these findings suggest a potential maintaining role of risky choice in gambling disorder, but do not support a maintaining role for impulsive choice.